Analisis Timbal (Pb) dan Tembaga (Cu) dalam Produk Burger Sapi yang Beredar di Kartasura secara Spektrofotometri Serapan Atom - Amanda Duta Wijaya; Endang Sri Rejeki; Reslely Harjanti (Fakultas Farmasi Universitas Setia Budi, 2011)
Beef burger is origin beef product that is milled and grounded, dashed with condiment then swirled with fat until it is mixed rolled out. Lead and copper in beef burger could be make toxicity if its rate exceed stipubting from BPOM which is for lead content may not exceed 2,0 mg/kg whereas copper may not exceed 20,0 mg/kg. The aim of the research was to know lead and copper content in beef burger products commercial in Kartasura by atomic absorption spectrophotometry. This research used 3 samples beef burger product. The sample was put in blender then put in oven at temperatur 1100 C until dry. The sampel was ashed in muffle furnace at temperatur 5500 C for5 hours. The sample was destructed with aquaregia (mixed HCl and HNO3 = 3:1) and dissolved with aquabidestillata, then analyzed by atomic absorption spectrophotometry at wavelength 283,3 nm. The result of qualitative analysis shown positive result because at condition analysis’s lead and copper element all samples gave absorption. The result of quantitative analysis rate of lead in sample A, B, C successively, that was: 0,2418 ± 0,0005 mg/kg; 0,2412 ± 0,0006mg/kg; 0,2398 mg/kg. The result of quantitative analysis rate of copper in sample A, B, C successively, that was:0,2886 mg/kg; 0,3312 ± 0,000001 mg/kg; 0,2956 ± 0,0012 mg/kg.